Toward early screening for early management of postnatal depression? Relationships between clinical signs present in the infant and underlying maternal postnatal depression - Julien-Sweerts, Sabrina; Rousselin, Sandie; Raffeneau, Florence; Xavier-David, Charlotte; Changeur, Violette; Apter, Gisèle; Romo, Lucia; Gicquel, Ludovic (Frontiers in Psychiatry, 2022)
Objective The objective was to screen for maternal postnatal depression (MPD) by administering the Edinburgh Postnatal Depression Scale (EPDS) during the first “peak” of incidence of MPD (i. e., between the 6th and the 10th week of the infant's life) and to therefore explore the relationship between mothers' EPDS scores and early clinical signs in the infant. We wanted to evaluate the relevance of a diagnostic tool that combines the EPDS with questions focused on clinical signs displayed by the infant. Participants Seven hundred and sixty seven mothers aged 18–46 (M = 30.5, SD = 4.9) participated in the study, representing 49.2% of all women who delivered in the study area during the research inclusion period. Main outcome measures: Sociodemographic data were collected. MPD was measured by EPDS (score ≥ 12). The presence of clinical signs in the infant was investigated by closed (i.e., yes or no) questions inquiring into whether the infant has or has had difficulty sleeping, feeding difficulties, crying difficult to calm, or other difficulties. Results The prevalence of MPD in our sample was 22.16%. The relationships between MPD and early clinical signs present in the infant, i.e., sleep difficulties, feeding problems, crying difficult to calm (p < 0.001), and other problems (p = 0.004), were very significant, as confirmed by a chi-square test of independence. In particular, sleep difficulties (OR = 2.05, CI 1.41–2.99) and feeding difficulties (OR = 1.59, CI 1.10–2.30) seemed to predict MPD. Conclusions Early clinical signs in the infant can alert the medical team to potential psychological suffering on the part of the mother, at which time the EPDS can be proposed. The use of this method has the potential to improve screening for, and therefore early management of, MPD.